Transforming Citizenships : Transgender Articulations of the Law - West, Isaac (Book collections on Project MUSE., 2013)
This book engages the performativity of citizenship as it relates to transgender individuals and advocacy groups. Instead of reading the law as a set of self-executing discourses, the author takes up transgender rights claims as performative productions of complex legal subjectivities capable of queering accepted understandings of genders, sexualities, and the normative forces of the law. Drawing on an expansive archive, from the correspondence of a trans woman arrested for using a public bathroom in Los Angeles in 1954 to contemporary lobbying efforts of national transgender advocacy organizations, the author advances a rethinking of law as capacious rhetorics of citizenship, justice, equality, and freedom. When approached from this perspective, citizenship can be recuperated from its status as the bad object of queer politics to better understand how legal discourses open up sites for identification across identity categories and enable political activities that escape the analytics of heteronormativity and homonationalism. --